Symulacyjna optymalizacja wyboru procedury klasyfikacyjnej dla danego typu danych - oprogramowanie komputerowe i wyniki badań - Walesiak, Marek; Dudek, Andrzej (Determination of optimal clustering procedure for a data set - computer program and empirical results, 2006)
In typical cluster analysis study eight major steps are distinguished (see Milligan [1996, 342 343]; Walesiak [2005]). Four of them represent the critical steps: decisions concerning variable normalisation formula, selection of a distance measure, selection of clustering method, determining the number of clusters. The article presents: a) determination of optimal clustering procedure for a data set by varying all combinations of normalization formulas, distance measures, and clustering methods. Nine paths of simulation was separated depends on variable scale of measurement in a data set; b) clusterSim computer program written in R and C++ languages; c) some empirical results of simulation study based on data matrix with growing number of objects and variables.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 120-129